Occupational asthma due to formaldehyde. - Burge, P S (1985)
Bronchial provocation studies on 15 workers occupationally exposed to formaldehyde are described. The results show that formaldehyde exposure can cause asthmatic reactions, and suggest that these are sometimes due to hypersensitivity and sometimes to a direct irritant effect. Three workers had classical occupational asthma caused by formaldehyde fumes, which was likely to be due to hypersensitivity, with late asthmatic reactions following formaldehyde exposure. Six workers developed immediate asthmatic reactions, which were likely to be due to a direct irritant effect as the reactions were shorter in duration than those seen after soluble allergen exposure and were closely related to histamine reactivity. The breathing zone concentrations of formaldehyde required to elicit these irritant reactions (mean 4.8 mg/m3) were higher than those encountered in buildings recently insulated with urea formaldehyde foam, but within levels sometimes found in industry.